Kemampuan Berpikir Kreatif Matematis Dan Self-Confidence Siswa Dengan Pendekatan Open-Ended - Handayani, Sugeng; Marwan, Marwan; Ansari, B.I. (SUKMA: Jurnal Pendidikan, 2022)
Mathematics is taught to guide students to think creatively in solving problems which encountered in everyday life. This study aims to determine the ability of mathematical creative thinking of students who take the learning by using the Open-Ended, self- confidence approach students who followed the learning by using the Open-Ended approach, and determine the interaction between the Open-Ended approaches with students’ level of ability (high, medium, and low) towards mathematical creative thinking abilities. This study is a quasi-experimental research design with pre-test post-test control group design . The population of this study were all eight grade students of Sukma Bangsa Pidie Junior High School with two samples (experimental and control classes) which is decided by using purposive sampling. Data collection was performed using two types of instruments, test and non-test instruments. The tests include mathematical creative thinking skills, and non-tests include the Self-Confidence questionnaire. Based on statistical data analysis using t-test at a significant level of 0.05, it is identified that 1) The ability of students’ mathematical creative thinking who learn using the Open-Ended approach is better than students who learn using conventional learning; 2) Students’ Self-Confidence who follow learning using the Open-Ended approach are better than students who obtain conventional learning; 3) There is no dealings between the Open-Ended approaches with students’ level of ability (high, medium, and low) toward the ability of students’ mathematical creative thinking skills.